Analysis of Science Process Skills in the Guided Inquiry Learning Model of Biotechnology Materials - Lailiyatus Sufriyah; Zulfiani Zulfiani; Dina Rahma Fadlilah (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
Scientific Process Skills (SPS) are essential competencies for students to face 21st-century challenges. However, learning processes in schools often overlook the development of these skills. One learning model considered effective in enhancing SPS is the Guided Inquiry model. This study aims to identify the profile of students’ SPS through the Guided Inquiry learning model on biotechnology material and to determine differences in SPS between students who experience Guided Inquiry learning and those who receive conventional instruction. The research was conducted in 2024 at a senior high school in Depok using a quasi-experimental method with a posttest-only control group design. The sample consisted of two-phase E classes selected through simple random sampling, each assigned as the control and experimental groups. Data collection used both test and non-test instruments: a posttest to assess SPS outcomes and an observation sheet to monitor SPS during learning. The results show that students’ SPS in the Guided Inquiry model vary across indicators, with the highest average score in communication (87.61%) and the lowest in prediction (49.52%). Independent Samples T-Test analysis revealed a significance value of 0.000 (< 0.05), indicating a statistically significant difference in SPS between the experimental and control groups. These findings suggest the Guided Inquiry model effectively enhances students’ scientific process skills in biotechnology learning